POLICY STRATEGY OF MARITIME POTENTIAL SERVICE (DISPOTMAR) NAVAL BASE V IN SUPPORTING THE DEVELOPMENT OF INDONESIAN MARITIME POTENTIALS - I Nyoman Astawa Yasa; Rian Prasetian; Raditiyo Dimas Mudjiono (Indonesian Naval Technology College STTAL, 2022)
The Maritime Potential Development Service (Dispotmar) of Naval Base V is one of the Central ImplementingElements at the Naval Base V level which is in charge of carrying out the function development andimplementation of maritime potential development activities. In order to support the development of maritimepotential, there are several problems that occur in the field of regional resilience development, socialcommunication, community service, maritime service industry, socialization of fishery laws and fulfillment ofinfrastructure. This research is expected to overcome some of the problems faced. The stages of the researchcarried out were identifying and evaluating internal and external factors, selecting strategies using the SWOTmethod, compiling alternative strategies and determining the priority strategies selected using Borda. The resultof this research find the WO 5 strategy as the higher priority value of 0.38 as , namely the preparation of a NCOlegal forms to be used as a guideline and basis for NCOs personnel by utilizing government program support andthe main task of Dispotmar as a coach for the maritime youth generations.Keywords: Policy Strategy, Dispotmar Naval Base V, SWOT, Bordas